Effects of Salt Stress on Ion and Lipidperoxidation Content in Green Beans Genotypes - YASAR, FIKRET (Asian Journal of Chemistry, 2010)
The response of 13 green bean genotypes used in this study to salt stress was found differently. Taking into consideration of all genotypes, generally, the genotypes showing better growth under salt stress had lower Na, higher K and Ca contents. Of green bean genotypes used this study; Ca contents of genotypes having higher fresh weight was found higher than those of genotypes having lower fresh weight under salt stress. Tolerant genotypes had higher K+/Na+ and Ca2+/Na+ ratios than sensitive genotypes. Differences between MDA contents of 13 green bean genotypes under grown salt stress were found significant. The lowest MDA content was obtained in GS57 showing the best growth under salinity. At the same time, this genotype had the highest K+ and Ca2+ content and the second lowest Na+ content. ES18 and GB64 genotypes also presented the same behaviours in salinity.